Besoins et dispositifs d'aide dans le contexte d'apprentissage des MOOC - Emmanuelle Chevry Pebayle; Isabelle Rossini (Centre National d'Enseignement à Distance, 2012)
The authors present here the results of a study on the difficulties of learners and trainers encountered in three MOOC as well as the proposed helps or assistances and how the learners used them. The article is divided into three parts. The first part presents the difficulties encountered by teachers and by learners when they are in a learning situation in a MOOC. It is a question of knowing whether they have experienced difficulties in terms of the disciplinary content, in the scenarisation or in the use of the tools. A statistical survey data analysis shows that the difficulties of the learners vary according to the different MOOC. The second part focuses on the difficulties experienced by the designers and the helps and the different pedagogical situations implemented in the MOOC eFAN-Maths by the teachers-designers, with a view to reducing the difficulties of the learners. It is a question of identifying, on the one hand, the different pedagogical situations occurring on the three MOOC studied. On the other hand, it is necessary to characterize these aids by explaining the intentions and the associated contexts, the strategies chosen by the designer and his expectations using the ISA model (Intentions Strategies Expectations). Finally, on the basis of the results of the survey and the interviews of the three MOOC designers, the third part emphasizes the role of social and numerical media in term of learners' assistance. Then the social artefact appears as an additional component to be considered in a learning situation in a CSLE (Computer Supported Learning Environment).